Shared Harvest : continuous cultivation for a better life - Fu, Yan, 1961-; Wang, Jianying, active 2018; Xu, Jingyue, active 2018 (London : Renmin University, 2018)
Social entrepreneurship is a new topic in the field of entrepreneurship. Shared Harvest is a social enterprise based on the model of Community Supported Agriculture (CSA), devoted to solving the problems of agricultural pollution, food safety, and rural sustainable development in China. Chinese agriculture is facing the challenges of multiple problems, such as an agricultural product safety crisis, environmental pollution, and a lack of mutual trust between producers and consumers.This case describes the social entrepreneurship and growth journey of Shared Harvest against such a background. Focusing on scaling its social entrepreneurial impact, Shared Harvest not only effectively operates a CSA farm that produces and distributes agricultural products in compliance with organic standards, but also explores new development paths to solve the problems of agriculture, rural areas, and farmers through food and farming education, building a food community, CSA alliances, training for new farmers, and environmental re-engineering in rural communities. It is worthwhile to explore how Shared Harvest and its founder, Yan Shi, continue scaling its social entrepreneurial impact.
Originally Published InFu, Y., Wang, J., & Xu, J. (2018). Shared Harvest: Continuous Cultivation for a Better Life. Beijing, China: Renmin University Business School.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social entrepreneurship -- China -- Case studies; Community-supported agriculture -- China -- Case studies